Fabrication and characterisation of Cobalt Chromium Molybdenum (CoCrMo) foams using slurry method - Ab Manaf, Nur Suliani (2018)
Cobalt Chromium Molybdenum (CoCrMo) is a metal foams that are widely used in the biomedical field of orthopedic applications. This research is intended to produce CoCrMo foam by using slurry method and to perform optimization on processing parameters slurry method in CoCrMo foam preparation by the orthogonal array L9 method. The slurry of CoCrMo is prepared by the mixing the binder materials and distilled water for an hour. Followed by mixing and stirring the CoCrMo powder for another 1 hour until it becomes slurries. Polyurethane (PU) foam is then impregnated into the slurry and dried at 40°C for a day in the oven. It was found that the possible composition were 60wt%, 65wt% and 70wt% for CoCrMo. This was followed by the appropriate sintering temperature results which were 1000°C, 1100°C and 1200°C with heating rate of 1.5°C/min, 1.0°C/min and 0.5°C/min. Moreover, for the soaking time factor, the relevant durations were 60, 90 and 120 minutes. The parameter that influence in the result was the composition that were in porosity and bulk density analysis. The optimum value of 54.42% was obtained for porosity was the composition at 60wt% CoCrMo, sintering temperature of 1100°C, heating rate of 1.5°C/min and soaking time of 60 minutes. In addition, the significant factors that influence the bulk density analysis of CoCrMo foam were the composition factor. The optimum sintering condition which resulted in bulk density analysis of 2.23g/cm3 was found to be a composition of CoCrMo at 60wt%, sintering temperature of 1000°C, heating rate of 1.5 °C/min and soaking time of 60 minutes. The present work shows that the optimisation of the sintering parameters has improved the physical properties of both the CoCrMo foams.